Security testing for mobile blockchain application - Ngai, Kevin Cai Hua (2019)
The number of blockchain applications are increasing with the growth in blockchain technology. More developers are leveraging their applications on the blockchain platform to fully utilise the benefits of a distributed and decentralised network. Hence, Blockchain technology can be integrated with mobile applications to explore new boundaries in the world of technology. Nonetheless, digital security is a major component in today’s world due to many cases of cyber attacks from around the world. Hence, security must not be neglected when employing blockchain technology on applications. For this project, security testing is performed on a mobile blockchain application created to perform data storage and transfer between the mobile interface and the blockchain network. The blockchain technology used for this project is Ethereum and the mobile application is created on the Android platform. There are a few security aspects which the project will focus on: Security on Ethereum, Integration between Android and Ethereum and Application Security. Security tests are performed for each aspect and the results, observations deduced from the tests will help to identify threats and possibly fix the vulnerabilities and issues that are detected.